Cost and Return Analysis of System of Rice Intensification (SRI): Evidence from Major Rice Producing Areas in Malaysia - Nur Fatin Munirah Aris; Fazleen Abdul Fatah (International Journal of Supply Chain Management, 2019)
Rice (Oryza sativa L.) is the staple food and being the most important ingredient of the food basket for most nations in Asia. The declining productivity of rice and its availability of per capita is therefore a policy concern. Nevertheless, the production of rice in Malaysia is primarily implemented by adopting the conventional technique. This technique has increased the production cost of rice and became a constraint to achieving the production potential for the farmer. Thus, the System of Rice Intensification (SRI) was introduced in the rice cultivation as a relevant innovation which to offset the high cost of the conventional technique. Besides, such technique also decreases the production cost, reduces yield gap and increases profits of the farmers with less agronomical inputs. SRI also minimizes water use by scientific water management. As a result, such water minimization increases the productivity of rice farms in Malaysia which subsequently has an enormous potential for resource conservation and sustainability. Therefore, this paper attempts to determine the profitability and the factors affecting SRI adoption among rice farmers. The result revealed that the yield can be increased by changing the management of plants, soil, water and nutrients. The multiple linear regression analysis indicated that age, educational level, field size, role of information and environment condition had a positive impact and significantly influenced SRI adoption. Considering the substantial advantages, the suitable strategy for upscaling the SRI adoption is required to accomplish sustainable agriculture and food security.